Association Between Vitamin D and Resistin in Postmenopausal Females With Altered Bone Health - Tariq, Sundus; Tariq, Saba; Khaliq, Saba; Baig, Mukhtiar; Murad, Manal Abdulaziz; Lone, Khalid Parvez (Frontiers in Endocrinology, 2021)
Background: Resistin is a relatively novel adipokine that has a role in bone remodeling and may regulate bone mineral density (BMD). Vitamin D and adipokines have a dynamic role in the body's various metabolic processes, including bone metabolism, and may alter bone metabolism in relation to each other. This study aimed to investigate the association between vitamin D and serum resistin levels in postmenopausal non-osteoporotic and osteoporotic females. Methods: This correlational analytical study was conducted on 161 postmenopausal females, divided into two groups, non-osteoporotic and osteoporotic, between 50-70 years. Bone mineral density (BMD) was assessed by dual-energy X-ray absorptiometry (DXA) scan. Serum resistin and vitamin D levels were analyzed by enzyme-linked immunosorbent assay (ELISA) method. Serum calcium, phosphate, and alkaline phosphatase with spectrophotometry. A correlation was checked using spearman's rho correlation coefficient, and multivariate stepwise regression analysis was used to predict serum resistin levels. Results: Postmenopausal females (n=161) having sufficient, insufficient and deficient levels of vitamin D were 87 (54.0%), 64 (39.8%) and 10 (6.2%) respectively. Lumbar spine BMD (p < 0.001), total hip BMD (p < 0.001) and serum resistin levels (p < 0.001) were significantly different between the two groups. There was a significant negative correlation between serum resistin and vitamin D in postmenopausal females (rho = -0.182, p = 0.021) and osteoporotic group (rho = -0.253, p = 0.019) but non-significant in non-osteoporotic group (rho = -0.077, p = 0.509). Serum vitamin D was found to be independent predictor of serum resistin levels, accounting for only 3% variance. Conclusion: Serum vitamin D levels were low while serum resistin levels were high in postmenopausal osteoporotic females and vitamin D is a negative predictor of serum resistin levels.